2015
DOI: 10.3390/ijerph120911037
|View full text |Cite
|
Sign up to set email alerts
|

Mental and Physical Symptoms of Female Rural Workers: Relation between Household and Rural Work

Abstract: This study aimed to investigate the relations among mental disorders, physical discomfort, household work and farm work among women. We conducted a cross-sectional study based on the administration of a structured questionnaire to 182 female farm workers. The data were analyzed by means of Poisson regression, where the significance level was set to 5%. Results indicated that 111 (61%) participants reported work-related mental disorders and physical discomfort was reported by 160 (87.9%). The participants with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
1
11
0
1
Order By: Relevance
“…Moreover, our results confirm that musculoskeletal disorders are the nonfatal injuries studied most in the agricultural sector (Fathallah 2010), mainly on dairy farms (Douphrate et al 2013). However, studies have highlighted the importance of an adequate psychosocial work environment, and the influence of stress and depression, on the mental health of farm workers (Melberg 2003;Kolstrup et al 2008;Wallis and Dollard 2008;Cezar-Vaz et al 2015).…”
Section: Major Current Issues Addressed By the Scientific Communitiessupporting
confidence: 79%
“…Moreover, our results confirm that musculoskeletal disorders are the nonfatal injuries studied most in the agricultural sector (Fathallah 2010), mainly on dairy farms (Douphrate et al 2013). However, studies have highlighted the importance of an adequate psychosocial work environment, and the influence of stress and depression, on the mental health of farm workers (Melberg 2003;Kolstrup et al 2008;Wallis and Dollard 2008;Cezar-Vaz et al 2015).…”
Section: Major Current Issues Addressed By the Scientific Communitiessupporting
confidence: 79%
“…However, in a different study conducted in Bangladesh, nearly half of the rural participants were engaged in income-generating activities (14) . In a study developed in Rio Grande do Sul, Brazil 96.7% of the participants performed agricultural and domestic work (15) , thus demonstrating physical overload and the vulnerability of these women. It is believed that there are variations in socio-cultural roles and their association with gender and the inhabited region, being rural or urban (16) .…”
Section: Introductionmentioning
confidence: 99%
“…This study corroborates the findings of the present study, since one of the types of medication used the most by women were for the nervous system, such as psychotropic drugs (22) . A study with farm workers in a rural area in Brazil found that the odds of mental disorders were higher among women with moderate or higher levels of physical discomfort and frustration with agricultural work (17) . Mental disorders are the main cause for the use of medication that acts on the nervous system (23) .…”
Section: Discussionmentioning
confidence: 99%
“…To define the workload required by agricultural tasks, the validated NASA Task Load Index (NASA-TLX) (15) was used. This scale was applied in previous studies (16)(17) and measures workload through six demands: mental (think, choose, calculate and decide); physical (push, pull, carry and weed); temporal (time needed for performing activities − much/little); performance (the activities are performed with more/less quality and speed); effort (physical and mental state for carrying out activities); and frustration (motivation, satisfaction, discouragement and irritation). The participants graded each demand from one to 20, to determine how heavy the workload was for each one.…”
Section: Methodsmentioning
confidence: 99%